Implementasi Cleaning Elderly Homes Volunteer oleh Mahasiswa KKN IAIN Syaikh Abdurrahman Siddik bersama PSM Desa Kacang Butor - Muhamad, Muhamad; Apriani, Via; Sari, Windy Rerdiya (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2023)
The population prevalence in Kacang Butor Village in September 2023 was recorded at 2,638 people with 928 heads of families divided into 1,398 people for men and 1,285 people for women. As for the data obtained with the classification of elderly people in Kacang Butor Village, there were 207 people, including 54 people in Air Behang Hamlet, 30 people in Bukit Indah Hamlet, 55 people in Kacang Butor Hamlet, and 68 people in Kepayang Hamlet. Elderly or the elderly phase is a period of human development where the function of the body's organs begins to decline. Based on the background of the characteristics of the elderly, IAIN KKN student Syaikh Abdurrahman Siddik Bangka Belitung carried out cleaning elderly home volunteer activities to improve the health and welfare of the population. In particular, cleaning elderly home volunteers aims to raise awareness among the local community about how important it is to look after the people around them, especially the elderly. This activity was approved by the village government and community social workers (PSM) because it was very relevant to conditions in the field. Apart from that, this activity was held for the first time in Kacang Butor Village. Therefore, the implementation of activities is carried out by KKN students, the community, and remains under the supervision of community social workers (PSM). Prevalensi penduduk di Desa Kacang Butor pada September 2023 tercatat sebanyak 2.638 jiwa dengan 928 kepala keluarga terbagi menjadi 1.398 jiwa untuk laki-laki dan 1.285 jiwa untuk perempuan. Adapun perolehan data dengan klasifikasi lansia di Desa Kacang Butor tercatat sebanyak 207 jiwa meliputi 54 jiwa Dusun Air Begantung, 30 jiwa Dusun Bukit Indah, 55 jiwa Dusun Kacang Butor, dan 68 jiwa Dusun Kepayang. Lansia atau fase manula adalah masa perkembangan manusia dimana fungsi organ tubuh mulai menurun. Berdasarkan latar belakang karakteristik lansia mahasiswa KKN IAIN Syaikh Abdurrahman Siddik Bangka Belitung mengusungkan kegiatan cleaning elderly home volunteer untuk meningkatkan derajat kesehatan dan kesejahteraan penduduk. Secara khusus cleaning elderly home volunteer bertujuan untuk menumbuhkan kesadaran bagi masyarakat sekitar betapa pentingnya menjaga orang sekitar terutama lansia. Kegiatan ini disetujui oleh pemerintah desa dan pekerja sosial masyarakat (PSM) karena sangat relevan dengan kondisi di lapangan. Selain itu, kegiatan ini baru pertama kali diadakan di Desa Kacang Butor. Oleh sebab itu, pelaksanaan kegiatan dilakukan oleh mahasiswa KKN, masyarakat, dan tetap dalam pengawasan pekerja sosial masyarakat (PSM).